2021
DOI: 10.1021/acs.jcim.1c00428
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation Free-Energy Toolkit: An Automated Alchemical Topology Builder

Abstract: Free-energy calculations play an important role in the application of computational chemistry to a range of fields, including protein biochemistry, rational drug design, or materials science. Importantly, the free-energy difference is directly related to experimentally measurable quantities such as partition and adsorption coefficients, water activity, and binding affinities. Among several techniques aimed at predicting free-energy differences, perturbation approaches, involving the alchemical transformation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…In the study introducing transformato (Wieder et al, 2022), we demonstrated that one can achieve very high accuracy with the CC/ SAI approach for (relative) solvation free energy differences. Our present results demonstrate that the approach can be extended to large-scale RBFE calculations and that, overall, the agreement with related approaches (Wang et al, 2015;Song et al, 2019;Gapsys et al, 2020;He et al, 2020;Petrov, 2021) is good.…”
Section: Concluding Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In the study introducing transformato (Wieder et al, 2022), we demonstrated that one can achieve very high accuracy with the CC/ SAI approach for (relative) solvation free energy differences. Our present results demonstrate that the approach can be extended to large-scale RBFE calculations and that, overall, the agreement with related approaches (Wang et al, 2015;Song et al, 2019;Gapsys et al, 2020;He et al, 2020;Petrov, 2021) is good.…”
Section: Concluding Discussionsupporting
confidence: 76%
“…They require significant computing resources and are comparatively slow; setting up the simulations and analysis procedures is difficult and tedious, even for experts. To make their utilization easier, several front ends to biomolecular simulation packages have been developed to help set up RBFE simulations ( Seeliger and de Groot, 2010 ; Gapsys et al, 2015 ; Loeffler et al, 2015 ; Wang et al, 2015 ; Zhang H. et al, 2021 ; Petrov, 2021 ). Here, we present a related tool, transformato, which, in contrast to most other tools, is not dependent on a particular simulation program.…”
Section: Introductionmentioning
confidence: 99%
“… 50 The different ligands under study were parameterized using the Automated Topology Builder web server (ATB) and adjusted to better match the GROMOS charges. 51 The python package SMArt 52 was used to build the reference state and perturbation topologies using a single topology approach, which contains the necessary extra atoms for all of the endstates as dummy particles. 53 , 54 To simplify the perturbation topology, the bond lengths of the five-member ring of indene, indole, and benzofurane remained constant.…”
Section: Methodsmentioning
confidence: 99%
“…Several approaches exist for the computational prediction of protein thermostability changes upon single-point mutations, ranging from detailed all-atom molecular dynamics (MD) simulations, simplified energy models, statistical approaches, and phylogenetic analyses to machine learning methods. MD simulations in explicit solvent evolved toward a promising tool in the prediction of protein thermostability although the computational expense often still hampers a high-throughput setup. However, this will be more and more facilitated by the increased calculation speed accompanied by pre- and postprocessing tools that make the setup of such calculations more user-friendly , as well as the establishment of best practices to set up and analyze such calculations. , The study of Gapsys et al showed that different force fields may perform quite differently in their ability to predict free-energy changes due to side-chain mutations. Based on this finding, they suggested a consensus approach, utilizing predictions in multiple force fields, that, together with increased sampling time, reached a prediction accuracy comparable to those obtained in experiments.…”
Section: Introductionmentioning
confidence: 99%